Fetal Tachycardia in the Delivery Room: Fetal Distress, Supraventricular Tachycardia, or Both? - Bhatia, Satvinder Singh; Burgess, Wendy H.; Skinner, Jonathan R. (American Journal of Perinatology Reports, 2020)
Background Supraventricular tachycardia (SVT) is seldom considered a cause for fetal tachycardia; commoner etiologies including maternal fever and fetal distress are usually envisaged. Fetal arrhythmia can be missed as a diagnosis, potentially leading to suboptimal management.Cases Three cases are described where detection of fetal tachycardia >200 beats per minute (bpm) at 36, 40, and 38 weeks gestation resulted in emergency cesarean section for presumed fetal distress. Retrospective review of the cardiotocograph in two cases revealed baseline heart rates 120 to 160 bpm, with loss of trace associated with auscultated rates over 200 bpm. The diagnosis of SVT was not initially considered and made later when the infants required cardioversion at the age of 3 weeks, 2 days, and 8 days, respectively. The 36-week infant required noninvasive ventilation for prematurity.Conclusion SVT should be actively considered in the differential diagnosis of fetal tachycardia. Unrecognized fetal SVT may result in avoidable caesarean for suspected fetal distress, with potential prematurity-related problems. The cardiotocograph can be helpful if showing contact loss associated with rapid heart rate auscultation. The antenatal detection of fetal SVT is important as it can allow anticipation and prevention of neonatal SVT, which is potentially life-threatening if not detected and treated promptly.
Keywords: fetal distress; fetal arrhythmia; fetal SVT; neonatal SVT